Penerapan Sistem Akuntansi Barang Jaminan dan Prosedur Akuntansi Pelunasan Gadai pada Pegadaian Kota Gunungsitoli - Kurniawan Sarototonafo Zai (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
A problem at PT. Pegadaian in Gunungsitoli City is the lack of understanding of the accounting system among employees. This is because some employees still lack an understanding of the accounting system, particularly when it is applied to the receipt and disbursement of collateral, and managers in decision-making. This requires more open internal and external relationships, and it is necessary to improve customer understanding of how the collateral receipt and disbursement system actually works. Many customers still lack a comprehensive understanding of the collateral receipt and disbursement system.The purpose of this study was to determine the implementation of the collateral accounting system and the accounting system for pawn repayment at the Gunungsitoli City pawnshop.Data collection techniques used interviews, observation, and desk research. The research used qualitative research. The sampling technique used saturated sampling, with a sample size of 20 employees from the total number of employees at the Gunungsitoli branch of the pawnshop.The results indicate that the implementation of the collateral receipt and pawn repayment system, specifically the disbursement of collateral, at PT. Pegadaian (Persero) Gunungsitoli branch is designed in such a way that it has a simple, easy-to-understand procedure, with minimal involvement of multiple departments. Documents are crucial to implementing a pawn accounting system because they serve as archives. The documents used at the Gunungsitoli branch of PT Pegadaian Persero partially meet the requirements and are complete enough to record collateral disbursement transactions.